ANALYSIS OF PRODUCT POSITIONING ON ASIAN MOBILE PHONE PRODUCTS IN MANADO - Roring, Dio Rio; Pangemanan, Sifrid S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Cellular phone that was once only used to send messages and get in touch with each other, has now turned into a lot of functions and is very sophisticated, with the development of mobile products makes a mobile phone into an object that is in need tape that used to have multiple mobile phone functions that have only by some well-known product now owned or installed into the phone - mobile phone often known by the mobile phone made ​​in asia or asian mobile phone such as: Oppo, Lenovo, HTC, Mito, ZTC, Nexian mobile phones that previously mobile phones that not have capabilities that have high brand value, because it saw the economic competition now finally they apply to adds some features that other mobile phone into their console at low prices.The key findings regarding the physical characteristic showed the top two considerations included: price and Quality.  The purpose of this research to identify the age, occupation and latest education of each customers  by creating a multidimensional scaling. With 100 respondents are contributed andMultidimensional Scaling method is used in this research. In this case, people in Manado have a different perception towards Mobile Phones. Mobile Phone branded Htchave attention from customers as best based on quality and Mobile Phone branded ZTC as the expensive based on price. The results of the analysis showed that others competitors have to increase their quality and adjust their price to compete and get attention from customers.   Keywords: product positioning, perceived price, quality.